Rational wiring of photosystem II to hierarchical indium tin oxide electrodes using redox polymers. Issue 12 (26th July 2016) - Sokol, Katarzyna P.; Mersch, Dirk; Hartmann, Volker; Zhang, Jenny Z.; Nowaczyk, Marc M.; Rögner, Matthias; Ruff, Adrian; Schuhmann, Wolfgang; Plumeré, Nicolas; Reisner, Erwin
Abstract : A rational approach for a photosystem II-based electrode assembly is described, integrating redox polymers with high surface area hierarchically structured electrodes. Abstract : Photosystem II (PSII) is a multi-subunit enzyme responsible for solar-driven water oxidation to release O2 and highly reducing electrons during photosynthesis. The study of PSII in protein film photoelectrochemistry sheds light into its biological function and provides a blueprint for artificial water-splitting systems. However, the integration of macromolecules, such as PSII, into hybrid bio-electrodes is often plagued by poor electrical wiring between the protein guest and the material host. Here, we report a new benchmark PSII–electrode system that combines the efficient wiring afforded by redox-active polymers with the high loading provided by hierarchically-structured inverse opal indium tin oxide (IO-ITO) electrodes. Compared to flat electrodes, the hierarchical IO-ITO electrodes enabled up to an approximately 50-fold increase in the immobilisation of an Os complex-modified and a phenothiazine-modified polymer. When the Os complex-modified polymer is co-adsorbed with PSII on the hierarchical electrodes, photocurrent densities of up to ∼410 μA cm −2 at 0.5 V vs. SHE were observed in the absence of diffusional mediators, demonstrating a substantially improved wiring of PSII to the IO-ITO electrode with the redox polymer. The high photocurrent density allowed for the quantification of O2 evolution, and a Faradaic efficiency of 85 ± 9% was measured. As such, we have demonstrated a high performing and fully integrated host–guest system with excellent electronic wiring and loading capacity. This assembly strategy may form the basis of all-integrated electrode designs for a wide range of biological and synthetic catalysts.